Etika dan Tata Krama dalam Keluarga: Tinjauan Atas Penafsiran QS. an-Nur [24]: 58 Studi Komparatif Tafsir As-Sya’rawy dan Tafsir Al-Azhar - Harahap, Al-Azri Hidayah; Anwar, Husnel; Damanik, Agusman (ANWARUL, 2023)
The aim of this research is to analyze Muhammad Mutawally as-Sya'rawy and Hamka's interpretation of ethics and manners in the family based on the QS. An-Nur [24]: 58 in their tafsir book and the similarities and differences in the interpretations of the two figures in interpreting the QS. An-Nur [24]: 58. This type of research is qualitative or library research by collecting various related literature and then analyzing it using the muqaran interpretation method with a descriptive-analysis approach. The data sources in this research consist of primary sources, namely the interpretation of the QS. An-Nur [24]: 58 in tafsir as-Sya'rawy and tafsir al-Azhar. Meanwhile, secondary data sources are books, scriptures, articles, journals and other scientific research related to the theme discussed. From this research, it was found that there are several similarities and differences in interpretation between as-Sya'rawy and Hamka in interpreting the QS. An-Nur [24]:58 in their two tafsir books. Even though they are both modern tafsir and use the same method and style of interpretation, namely tafsir bi ar-ra'yi and adabi ijtima'i style, these two tafsir books still have significant differences. Differences in interpretation are found more often than similarities in interpretation. Similarities in interpretation are only found in matters of a principal or legal and basic ethical nature such as the main meaning of the verse, the laws contained in the verse and the three time limits for intimate parts that already exist in the text of the verse. Meanwhile, the differences occur due to the different social and social contexts between the two authors, because this interpretation uses the adabi ijtima'i style which makes the interpretation of the Qur'an a tool to improve the social conditions of society, the existing interpretations are also adapted to the social context of the local community. respectively, namely Egypt and Indonesia. Among the ethics and manners in QS. An-Nur [24]:58 in the tafsir as-Sya'rawy and tafsir al-Azhar, namely, first, asking for permission. Second, maintain the honor of family members. Third, respect the privacy of family members at home. Fourth, know the times when you are allowed and not allowed to visit. Fifth, maintain the stability of the physical, spiritual and psychological aspects of family members.